Pemetaan Tema Penelitian Tentang Manajemen Strategi dan Pemasaran: Analisis Bibliometrik - Sanjaya, Febry Prima; Aisyah, Vella Nur; Handriana, Tanti (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
This research aims to map research themes related to strategic management and marketing. The research method used is bibliometric analysis, where the research data source comes from the Scopus database. This study found that these two disciplines are closely related, with themes such as stakeholder engagement, employee participation, and human resource management being the main focus of the research—a new theme developing marketing strategy. A marketing strategy is a detailed plan that formulates how a company will achieve its marketing and business goals by identifying target markets, competitors, and the resources used. This research suggests future research to reveal more detailed insights into how companies develop, implement, and evaluate marketing strategies in various business situations. These findings imply the importance of integrating aspects of these two disciplines in the development of successful business strategies.